Twelve-month comparative analysis of clinical outcomes using biodegradable polymer–coated everolimus-eluting stents versus durable polymer–coated everolimus-eluting stents in all-comer patients - Abhyankar, Atul (Indian Heart J, 2019)
AIM: The purpose of the present study was to examine whether clinical differences exist between the biodegradable polymer (BDP)–coated Tetrilimus everolimus-eluting stent (EES) and the durable polymer (DP)–coated Xience EES by comparing the major adverse cardiac event (MACE) rate at 12 months in all-comer patients. METHODS: This study was designed as a multicentre, observational, retrospective, investigator-initiated study between January 2016 and October 2016. Two hundred thirteen patients who underwent percutaneous coronary intervention (PCI) with the BDP-EES were compared with 204 patients who underwent PCI with the DP-EES, irrespective of lesion complexity, comorbidities and acute presentation. The primary end point was MACE defined as a composite of cardiac death, myocardial infarction and target lesion revascularization. RESULTS: Baseline clinical and lesion characteristics of both the groups were similar, although the BDP-EES group had a significantly higher number of patients with diabetes mellitus (39.9% vs. 30.4%; p = 0.042) and type C lesion (67.4% vs. 48.1%; p < 0.001) than the DP-EES group. The 12-month MACE rate was 4.2% for the BDP-EES group versus 4.9% for the DP-EES group (p = 0.740). Mortality was lower in the BDP-EES group than in the DP-EES group (0.9% vs. 2.0%; p = 0.441). CONCLUSION: The present comparative analysis shows that the BDP-coated Tetrilimus EES was as safe and effective as the DP-coated Xience EES during the 12-month follow-up period despite complex lesion characteristics.